Energy management for a community-level integrated energy system with photovoltaic prosumers based on bargaining theory. (15th June 2021) - Jiang, Aihua; Yuan, Huihong; Li, Delong
Abstract: The game theory is a powerful and helpful approach to deal with the complicated relationship between participants efficiently. The Nash bargaining theory, one of the branches of cooperative game, is particularly suitable for the conflict of interest among the participants with interactive characteristics. This study analyzes the economic interaction between the community energy manager and the photovoltaic prosumers from a cooperative perspective. An incentive mechanism based on Nash bargaining theory to encourage the prosumers to actively participate in energy management is developed. In the proposed bargaining-based and cooperative model, the community energy manager as an integrated energy provider, is willing to give some rewards to the prosumers to stimulate them to cooperate with itself (i.e., the community energy manager). A photovoltaic prosumer who may behave as an energy buyer or seller determines the exchanged energy through bargaining with the community energy manager to achieve utility maximization. In the proposed model, the prosumers and the community energy manager are cooperative and mutually beneficial rather than a master-slave relationship. This study also provides an analysis of the relationship between the Nash bargaining problem and the social welfare function, illustrating that solving the Nash bargaining problem can obtain a social optimum. Moreover, a distributed algorithm with higher reliability and fault tolerance compared with the central approach is designed to solve the Nash bargaining problem with minimum information so that the privacy of the photovoltaic prosumers can be protected. Numerical studies based on realistic data demonstrate that both the photovoltaic prosumers and the community energy manager can obtain more benefits from the Nash bargaining cooperative model compared with a Stackelberg game method. Highlights: Optimal decisions of the players based on Nash bargaining theory. A model to help the prosumers to actively cooperate with the energy manager. Relationship between social welfare and the Nash bargaining problem. Obtaining social optimum through solving the proposed model. Improving the benefits of the energy manager and prosumers.